Konsep Jiwa Menurut Al-Razi: Tumpuan Terhadap Perihal Jiwa Setelah Berpisah Daripada Jasad: The Concept of the Soul According to Al-Razi: Focusing About the Soul after Being Separated from the Body - Sa’ari, Che Zarrina; Mohd Akib, Mohd Manawi (Online Journal of Research in Islamic Studies, 2018)
The concept of soul is one of the themes of discussion among earlier philosophers and then by Muslim philosophers such as Ibn Sina, al-Ghazali, al-Razi and others. Psychology disclosed in recent western studies views people merely from their material aspects with no association with religion. This concept brought by the west is more geared towards the introduction of the essence and character of the human being from the physical point of view without considering their spiritual point of views. Hence, it is the reason why people neglect the purpose of their creation and the next destination of the afterlife. This article highlights one of the questions regarding the concept of the soul according to Fakhr al-Din al-Razi, a Muslim scholar who was also described as an encyclopedic scholar, based on his works, to see the continuation of his views on the issue. Among the issues highlighted is that the enjoyment of the soul is more perfect, noble, significant and more feasible to be associated with the pursuit of happiness rather than bodily harmony; the ultimate happiness is the happiness acquired by human being in the hereafter; the punishment and suffering of the spirit in the Hereafter is stronger than worldly punishment and such punishment will be felt by the ignorant andthe vile hearted.